Dante in the long nineteenth century : nationality, identity, and appropriation - Audeh, Aida.; Havely, N. R. (Oxford : Oxford University Press, 2012)
These essays provides an account of Dante's reception in a range of media-visual art, literature, theatre, cinema, and music-from the late 18th century through to the early 20th and explores various appropriations and interpretations of his works and persona during the era of modernization in Europe, the USA, and beyond.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Dante Alighieri, -- 1265-1321 -- Appreciation -- History -- 19th century; Dante Alighieri, -- 1265-1321 -- Influence -- History -- 19th century; Intellectual life -- History -- 19th century